The Use of Youtube to Enhance Students’ Participation in Distance Learning Mode - Manalu, Camelia (Universitas Veteran Bangun Nusantara, 2022)
Increasing students’ participation is the central issue in distance learning mode during the pandemic. A teacher must be able to give maximum effort in teaching in the classroom, for example, by using ICT. This study aims to find out whether using YouTube can increase students’ participation in distance learning. The design of this research is classroom action research (CAR), with the subject of the research was 21 students of class XI IPS at SMAN 6 Tualang. This research was conducted in one cycle consisting of 5 online class meetings that used Youtube. The findings showed that by using Youtube, the participation and activeness of the students increased, which could be seen from actively asking questions, being enthusiastic in answering questions, and enjoying the learning process.